A case of spontaneous regression of pulmonary mucosa-associated lymphoid tissue (MALT) type lymphoma with Sjögren's syndrome treated with methotrexate for rheumatoid arthritis. (2015) - Yasui, Hideki; Nakamura, Yutaro; Hasegawa, Hirotsugu; Fujisawa, Tomoyuki; Enomoto, Noriyuki; Inui, Naoki; Fukuoka, Junya; Suda, Takafumi
Abstract: A 72-year-old man who had suffered from rheumatoid arthritis (RA) and Sjögren's syndrome (Sjs) since he was 66 years of age had been treated with methotrexate (MTX) for six years. He presented with a cough, sputum and dyspnea on exertion, and computed tomography findings showed multiple ground-glass opacities in both of his lungs. A biopsy of the lungs revealed low-grade mucosa-associated lymphoid tissue (MALT) type B-cell non-Hodgkin's lymphoma. Spontaneous complete remission of the lymphoma was achieved six months after withdrawing immune suppression with MTX. To our knowledge, no previous cases of spontaneous regression of pulmonary MALT-type lymphoma with Sjs treated with MTX for RA have been reported. Patients on MTX who are being treated for RA should be carefully monitored, especially when they have been diagnosed with coexistent Sjs.